Thermal analysis of thin-walled deployable composite boom in simulated space environment. (1st August 2017) - Bai, J.B.; Shenoi, R.A.; Xiong, J.J.
Abstract: This paper seeks to investigate thermal behaviour of a thin-walled deployable composite boom (DCB) in a space environment using ground thermal-vacuum test and FEA methods. Thermal tests simulating a space environment include three key conditions, namely ultra-high level of vacuum (lower than 10 −5  Pa), heat sink (−180 °C) that is realized using black panels with the liquid-nitrogen cooling system and thermal loading that is achieved through infrared lamps. The thermal tests of the DCB under seven typical heat fluxes were conducted to characterize heat transfer mechanisms and to obtain temperature fields. The basic heat transfer methods for the DCB in a space environment were surface radiation, cavity radiation and heat conduction. These led to significant temperature difference and gradient occurring on the irradiated and shadowed parts of the DCB at nighttime and daytime. FE models were established to predict temperature fields and thermally induced deformation. Good correlation was achieved between experimental and numerical results.